May I speak? Perceptions on ethical concerns and power while developing software in AI teams - Guimarães, Gabriel M. C.; Rocha Filho, Geraldo Pereira; Marques, Gilmar dos Santos; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Context: As Artificial Intelligence (AI) technologies increasingly influence decision-making processes, ethical concerns in AI development have gained significant attention. However, most research in this area focuses on high-level decision-makers or large technology corporations in the Global North, overlooking the lived experiences of software engineers in underrepresented contexts. Goal: This study investigates how Brazilian software engineers working in AI teams at a mid-sized company perceive ethical principles, navigate ethical dilemmas, and respond to emerging ethical concerns in their everyday work. The focus is on understanding how Junior, Mid-Level, and Senior developers interpret and apply ethical frameworks during the concrete development of AI systems such as classifiers, image generators, and object detectors. Method: A mixed-methods approach was adopted, combining data from 18 survey responses and 8 in-depth semi-structured interviews. The qualitative data were analyzed using a combination of inductive and deductive coding to identify recurring patterns, ethical challenges, and coping strategies. Results: Findings indicate that while participants are generally aware of key ethical principles—such as fairness, transparency, and accountability—their ability to act on ethical concerns is limited by factors including organizational hierarchies, lack of formal ethical training, and insufficient autonomy in design decisions. Ethical deliberation is often informal, reactive, and constrained by resource and power asymmetries. Conclusion: This research highlights the ethical agency of AI practitioners in the Global South and contributes to expanding the geographical and professional scope of AI ethics literature. It emphasizes the urgent need for organizational structures that empower developers to raise, discuss, and resolve ethical issues throughout the AI development lifecycle.